E-sport: Persepsi, Kompetisi Digital, dan Lokalitas (Studi Kasus Komunitas Unhas E-sport) - Akbar, Fadli (Universitas Muslim Maros, 2025)
E-sport have evolved from a form of entertainment into a global industry with significant social, economic, and cultural impacts. While most studies focus more on negative impact of e-sport, very limited studies on the positive impact on this kind of sport, particularly among university students. This article explores e-sports practices within the university environment as a form of digital competition that goes beyond entertainment and becomes a medium for identity production, symbolic capital, as well as local expression. Using a qualitative approach and a case study of the Unhas E-sport community, data were collected through participant observation and in-depth interviews with ten informants, consisting of three e-sport professional players, four e-sport fans, and three e-sport tournament organizers. The findings reveal four key points: first, e-sports is perceived not merely as gaming, but as a career path and form of digital labor requiring discipline and strategy; second, campus-level tournaments are organized professionally, demanding intensive preparation and high mental resilience; third, the competition process involves media distribution strategies that construct reputation and symbolic capital; and fourth, e-sports practices reflect Makassar’s local expressions through team identity, cultural narratives, and the use of digital spaces. Overall, e-sports functions as a symbolic arena and microeconomic environment that fuses global gaming culture with local values, while also shaping a new digital habitus among university students.